Post-weaning Social Isolation in Male and Female Prairie Voles: Impacts on Central and Peripheral Immune System - Donovan, Meghan L.; Chun, Eileen K.; Liu, Yan; Wang, Zuoxin (Frontiers in Behavioral Neuroscience, 2022)
The socially monogamous prairie vole (Microtus ochrogaster) offers a unique opportunity to examine the impacts of adolescent social isolation on the brain, immune system, and behavior. In the current study, male and female prairie voles were randomly assigned to be housed alone or with a same-sex cagemate after weaning (i.e. on postnatal day 21-22) for a six-week period. Thereafter, subjects were tested for anxiety-like and depressive-like behaviors using the elevated plus maze (EPM) and Forced Swim Test (FST), respectively. Blood was collected to measure peripheral cytokine levels, and brain tissue was processed for microglial density in various brain regions, including the Nucleus Accumbens (NAcc), Medial Amygdala (MeA), Central Amygdala (CeA), Bed Nucleus of the Stria Terminalis (BNST), and Paraventricular Nucleus of the Hypothalamus (PVN). Sex differences were found in EPM and FST behaviors, where male voles had significantly lower total arm entries in the EPM as well as lower latency to immobility in the FST compared to females. A sex by treatment effect was found in peripheral IL-1 levels, where isolated males had a lower level of IL-1 compared to cohoused females. Post-weaning social isolation also altered microglial density in a brain region-specific manner. Isolated voles had higher microglial density in the NAcc, MeA, and CeA, but lower microglial density in the dorsal BNST. Cohoused male voles also had higher microglial density in the PVN compared to cohoused females. Taken together, these data suggest that post-weaning social housing environments can alter peripheral and central immune systems in prairie voles, highlighting a potential role for the immune system in shaping isolation-induced alterations to the brain and behavior.